Design and Development ofa Mirror Effect Control Prosthetic Hand with Force Sensing - Maryam Hanan Yahya; Norhazimi Hamzah; Azizul Othman; Anis Diyana Rosli; Rohaiza Baharudin; Adi Izhar Che Ani (Universitas Ahmad Dahlan, 2017)
Some of the already available prosthetic hands in the market are operated in open loop, without any feedback and expensive. This system counters those by having the prosthetic hand printed using 3D printer and consist of a feedback sensor to make it a closed loop system. The system generally consists of two sections, mainly Finger Input and Prosthetic Output. The two sections communicate wirelessly for data transferring. The main purpose of the system is to control the prosthetic hand wirelessly using the Mirror Glove by performing a mirror effect that will translate movement from the glove onto the prosthetic hand. The Mirror Glove monitors the movements/bending of each fingers using force sensitive sensor. The prosthetic hand also has a sensor known as force sensitive resistor. The sensors will feedback the pressure on the prosthetic hand during object grasping, allowing the prosthetic hand to grasp delicate object without damaging it. Overall, the system will imitate the flex and relaxing of fingers inside the Mirror Glove and wirelessly control distant prosthetic hand to imitate the human hand.